SEA SURFACE TEMPERATURE ANOMALY IN SOUTH CENTRAL VIETNAM WATERS RELATED TO ENSO PHENOMENON - Tac, Vu Van; Hai, Doan Nhu; Son, Tong Phuoc Hoang; Tien, Ngo Manh; Khang, Nguyen Hoang Thai; Quang, Phan (Vietnam Journal of Marine Science and Technology, 2017)
Sea surface temperature (SST) in Bien Dong is well known as a parameter strongly influenced by the El Niño southern oscillation (ENSO). SST in South Central waters of Vietnam (SCWV) was analysed using OISST (Optimum Interpolation Sea Surface Temperature) daily data from NOAA. The results showed a clear pattern of ENSO impacts on SST in the South Central Vietnam. The average SST anomaly of South Central Vietnam had great value, ranking from -2.9 to 3.1. However, SST anomaly was not well corellated to the ONI index, especially for La Niña years. In weak to moderate ENSO years, SST anomalies were higher than those of the strong to very strong ENSO years. In fall (September to November) before La Niña year, average SST decreased by 0.4°C in comparison with El Niño or neutral years. In winter (December to February), average SST increased 0.6°C in El Niño years, and decreased 0.33°C in La Niña years. In spring (March to May), average SST was not much different between La Niña and normal years, but increased 0.44°C in El Niño years. However, in summer (Junuary to August), average SST in El Niño years decreased 0.53°C in comparison to La Niña and neutral years. In addition, average SST in the SCWV increased from 0.12 - 0.25°C in every decade, and increased 0.4°C since 1981. However, in the winter the average SST of SCWV decreased 0.1°C since 1981.